نظام الصرف وتقلبات سعر الصرف مع الإشارة إلى حالة الجزائر - زاهر خالد; جنيدي مراد (جامعة الوادي University Of Eloued, 2024)
سعت هذه الدراسة إلى البحث في أنظمة سعر الصرف من حيث تفاعلها مع تقلبات سعر الصرف، فتوصلت إلى أنه في إطار الربط الجامد والزاحف لا تملك السلطات النقدية حرية حقيقة ولا شبكة أمان لمواجهة الصدمات الحقيقية، إلا من خلال التدخل الرسمي، أما في إطار النظام العائم فإن التدخلات الرسمية في سوق الصرف الأجنبي ورغم الضرر التي تحدثه على مصداقية السياسة النقدية فإنها ملجأ العديد من الدول النامية والناشئة برغم ما يفترض في النظام العائم من عدم تدخل السلطات النقدية مع قوى السوق، وذلك من أجل تهدئة التقلبات وظروف السوق غير المنتظمة..This study sought to investigate the exchange rate systems and arrangements in terms of their interaction with exchange rate fluctuations. It concluded that in the framework of the rigid and crawling peg, the monetary authorities do not have real freedom nor a safety net to face real shocks, except through official intervention. Official interventions in the foreign exchange market and despite the harm they cause to the credibility of the monetary policy, they are the refuge of many developing and emerging countries despite what is assumed in the floating system of non-interference of the authorities themselves, in order to calm the fluctuations and the market conditions, that is, to influence the level of the exchange rate within the framework of its policy With all the debate about the effectiveness of these official interventions
Exchange system and the exchange rate fluctuations with reference to the case of Algeria
Keywords: التدخل الرسمي; Official Intervention; نظام سعر الصرف; التعويم; سوق الصرف الأجنبي; Exchange Rate Regime; Floating; Foreign Exchange